Applying the triads method in the validation of dietary intake using biomarkers - Yokota, Renata Tiene de Carvalho (2010)
The triads method is applied in validation studies of dietary intake to evaluate the correlation between three measurements (food frequency questionnaire, reference method and biomarker) and the true intake using validity coefficients (ρ). The main advantage of this technique is the inclusion of the biomarker, which presents independent errors compared with those of the traditional methods. The method assumes the linearity between the three measurements and the true intake and independence between the three measurement errors. Limitations of this technique include the occurrence of ρ > 1, known as “Heywood case”, and the existence of negative correlations, which do not allow the calculation of ρ. The objective of this review is to present the concept of the method, describe its application and examine the validation studies of dietary intake that use the triads method. We also conceptualize the “bootstrap” method, used to estimate the confidence intervals of the validity coefficients. ______________________________________________________________________________________________________________ RESUMO